Paleoenvironmental Changes for the Last 3000 Cal Years BP in the Pueyrredón Lake Basin, Southern Patagonia, Argentina - Marcos, Maria Alejandra (2022)
Patagonian shrub and ecotonal communities were sensitive to past environmental changes and thus may also be affected by future ones. Therefore, their paleoecological study constitutes a valuable tool to understand the way in which these plant communities respond to the forcings responsible for environmental variability. The aim of this paper is to reconstruct the vegetation dynamics of the Pueyrredón Lake area (47°25′55′′ S; 72°0.7′7′′ W) for the last 3000 cal yr BP and to contextualize these changes in a regional paleoclimatic framework. The results indicate that at the beginning of the 2900 cal yr BP, the vegetation in the northwest of Santa Cruz, Argentinian Patagonia, was represented by a grass-shrub steppe associated with forest–shrub steppe ecotonal elements. This information correlates with the larger-scale environmental inferences described for the period, which indicate an increase in moisture availability due to the weakening of the westerly winds. A marked change to arid conditions is indicated in the last 1050 cal yr BP, with the establishment and development of different shrub steppe communities and the lack of ecotonal elements. Although vegetation was sensitive to changes in moisture conditions related to the variability of the westerly winds, there is evidence of differences in the composition of shrub vegetation regarding the sequences analyzed. Variations in pollen proportions of the shrub steppes in the Pueyrredón Lake area suggest that changes in vegetation are not only due to climate variability but also local factors in the areas where shrub communities grow. The integration of the information with other Patagonian sequences allowed to frame these changes in a regional context. The results obtained provide useful information to understand the way vegetation changed in the past and the manner in which it may respond to future changes.